Korelasi Penguasaan Bunpou III dan Kemampuan Dokkai I Pada Mahasiswa Semester III Program Studi Pendidikan Bahasa Jepang Universitas Negeri Jakarta - Adinda Mia; Nia Setiawati; Poppy Rahayu (Universitas Negeri Jakarta, 2025)
This study aims to examine the correlation between the mastery of Bunpou III and the ability of Dokkai I in the 3rd semester students of the Japanese Language Education Study Program, State University of Jakarta. This research is based on the results of a student questionnaire which states that the Dokkai test item on N3 is the most difficult part to do because of the complex sentence patterns. 20 students participating in the Dokkai I course were sampled, because Dokkai I was a beginner step in preparing students to enter reading material at the N3 level. This study uses the correlational method with the final exam test as the instrument that has been validity tested by an Expert Judgment, as well as a questionnaire to determine response of the most influenced components of Dokkai I ability. The data collection technique uses the UAS value documentation. The conclusion of this study is that the correlation value of the Bunpou III mastery with the Dokkai I ability is -0.091 and included in the category of a weak correlation level. This is because the characteristics of reading according to experts are not only based on the ability to master grammar. The results of student responses indicate that the the most influenced components of Dokkai I ability are kanji by 45% and vocabulary by 45%.